Końcowa faza procesu twórczego – o pracy Kazimierza Przerwy-Tetmajera nad własnymi tekstami przed oddaniem ich do druku - Grzelak, Izabela (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The article analyzes the manuscript of a short story, Rzeźbiarz Merten, written by Tetmajer, one of the most known Polish poets at the turn of the 19th and 20th century. The author of this article tries to examine Tetmajer’s writing process. The scholar tries to prove also that this handwriting of Rzeźbiarz Merten is actually an autograph.